Resources
Testimonials
Plans
Sign in
Sign up
Resources
Testimonials
Plans
AI tutor
Welcome to Bytelearn!
Let’s check out your problem:
If
f
(
1
)
=
2
f(1)=2
f
(
1
)
=
2
and
f
(
n
)
=
f
(
n
−
1
)
2
+
1
f(n)=f(n-1)^{2}+1
f
(
n
)
=
f
(
n
−
1
)
2
+
1
then find the value of
f
(
4
)
f(4)
f
(
4
)
.
\newline
Answer:
View step-by-step help
Home
Math Problems
Algebra 2
Evaluate expression when a complex numbers and a variable term is given
Full solution
Q.
If
f
(
1
)
=
2
f(1)=2
f
(
1
)
=
2
and
f
(
n
)
=
f
(
n
−
1
)
2
+
1
f(n)=f(n-1)^{2}+1
f
(
n
)
=
f
(
n
−
1
)
2
+
1
then find the value of
f
(
4
)
f(4)
f
(
4
)
.
\newline
Answer:
Calculate
f
(
2
)
f(2)
f
(
2
)
:
Given
f
(
1
)
=
2
f(1) = 2
f
(
1
)
=
2
, we need to find
f
(
2
)
f(2)
f
(
2
)
using the recursive formula
f
(
n
)
=
f
(
n
−
1
)
2
+
1
f(n) = f(n-1)^{2} + 1
f
(
n
)
=
f
(
n
−
1
)
2
+
1
.
f
(
2
)
=
f
(
1
)
2
+
1
=
2
2
+
1
=
4
+
1
=
5
f(2) = f(1)^{2} + 1 = 2^2 + 1 = 4 + 1 = 5
f
(
2
)
=
f
(
1
)
2
+
1
=
2
2
+
1
=
4
+
1
=
5
.
Calculate
f
(
3
)
f(3)
f
(
3
)
:
Now, we find
f
(
3
)
f(3)
f
(
3
)
using the value of
f
(
2
)
f(2)
f
(
2
)
we just calculated.
f
(
3
)
=
f
(
2
)
2
+
1
=
5
2
+
1
=
25
+
1
=
26
f(3) = f(2)^{2} + 1 = 5^2 + 1 = 25 + 1 = 26
f
(
3
)
=
f
(
2
)
2
+
1
=
5
2
+
1
=
25
+
1
=
26
.
Calculate
f
(
4
)
f(4)
f
(
4
)
:
Finally, we find
f
(
4
)
f(4)
f
(
4
)
using the value of
f
(
3
)
f(3)
f
(
3
)
.
f
(
4
)
=
f
(
3
)
2
+
1
=
2
6
2
+
1
=
676
+
1
=
677
f(4) = f(3)^{2} + 1 = 26^{2} + 1 = 676 + 1 = 677
f
(
4
)
=
f
(
3
)
2
+
1
=
2
6
2
+
1
=
676
+
1
=
677
.
More problems from Evaluate expression when a complex numbers and a variable term is given
Question
Simplify.
\newline
8
i
+
6
i
8i + 6i
8
i
+
6
i
\newline
\newline
Write your answer in the form
a
+
b
i
a + bi
a
+
bi
.
Get tutor help
Posted 9 months ago
Question
Find the complex conjugate of the given number.
\newline
4
+
10
i
4 + 10i
4
+
10
i
\newline
\newline
Write your answer in the form
a
+
b
i
a + bi
a
+
bi
.
Get tutor help
Posted 9 months ago
Question
Simplify.
\newline
−
4
i
−
9
i
\frac{{-4i}}{{-9i}}
−
9
i
−
4
i
\newline
\newline
Write your simplified answer in the form
a
+
b
i
a + bi
a
+
bi
.
Get tutor help
Posted 9 months ago
Question
Combine the like terms to create an equivalent expression.
\newline
7
k
−
k
+
19
=
0
7k-k+19=\boxed{\phantom{0}}
7
k
−
k
+
19
=
0
Get tutor help
Posted 1 year ago
Question
Apply the distributive property to factor out the greatest common factor.
\newline
9
+
12
n
=
9+12 n=
9
+
12
n
=
Get tutor help
Posted 9 months ago
Question
Solve the equation.
\newline
12
=
n
−
9
n
=
□
\begin{aligned} & 12=n-9 \\ n= & \square \end{aligned}
n
=
12
=
n
−
9
□
Get tutor help
Posted 1 year ago
Question
What is the amplitude of
y
=
−
sin
(
8
x
−
3
)
+
5
y=-\sin (8 x-3)+5
y
=
−
sin
(
8
x
−
3
)
+
5
?
\newline
units
Get tutor help
Posted 1 year ago
Question
What is the period of
\newline
y
=
4
sin
(
−
2
x
+
7
)
−
1
?
y=4 \sin (-2 x+7)-1 \text { ? }
y
=
4
sin
(
−
2
x
+
7
)
−
1
?
\newline
Give an exact value.
\newline
units
Get tutor help
Posted 1 year ago
Question
3
⋅
(
3
+
20
i
)
=
3 \cdot(3+20 i)=
3
⋅
(
3
+
20
i
)
=
\newline
Your answer should be a complex number in the form
a
+
b
i
a+b i
a
+
bi
where
a
a
a
and
b
b
b
are real numbers.
Get tutor help
Posted 1 year ago
Question
(
35
−
23
i
)
+
(
13
+
25
i
)
=
(35-23 i)+(13+25 i)=
(
35
−
23
i
)
+
(
13
+
25
i
)
=
\newline
Express your answer in the form
(
a
+
b
i
)
(a+b i)
(
a
+
bi
)
.
Get tutor help
Posted 1 year ago
Related topics
Algebra - Order of Operations
Algebra - Distributive Property
`X` and `Y` Axes
Geometry - Scalene Triangle
Common Multiple
Geometry - Quadrant